SISTEM PEMESANAN COKLAT OLAHAN PADA PERUSAHAAN MINANG KAKAO - Yoga Permana Agung (2023)
Minang Kakao is a company that sells processed chocolate. Currently, theordering process at Minang Kakao is done offline and online,for offline customers must come directly to the place to make order transactions. This causes ordering activities to not run effectively and efficiently. And for online ordering can be through a third party marketplace but the shortcomings of the data are still inaccurate / unstructured, additional fees for the marketplace, and other obstacles. Web and mobile-based processed chocolate ordering information systems are used to make it easier for customers to make transactions without having to come directly to the place. The system development method used in this research is the waterfall method. The waterfall method is a method that is carried out sequentially. In the ordering system the author uses UML and MYSQL diagrams in processing data and this system is built using HTML, PHP, Flutter, Laravel programming languages as program processing. The result of this research is a computerized processed chocolate ordering system and the system can accommodate sales data. After this ordering system research is completed, the author hopes to make it easier for Minang Kakao to manage sales data and make it easier for consumers to make processed chocolate ordering transactions.